Jogo “sobe e desce”: operações matemáticas no 6º ano do ensino fundamental - GOMES, Julielson Pinheiro (2019)
In developing the theme "GAME “UP AND DOWN”: MATHEMATICAL OPERATIONS IN THE 6TH YEAR OF FUNDAMENTAL EDUCATION "for the mentioned work, it is looking for to use different methodologies to be worked with the students of the Santo André Quilombola School (attached to the Benvinda School of Araújo Pontes - Abaetetuba / Pará), who are starting the 6th year seeking to contribute to the methodologies developed in the classroom, present new ways of approaching mathematics, enhancing students' curiosity and interest, especially in mathematics, which is labeled as a discipline difficult to understand and out of reality. Thus, offer practical subsidies for students to learn the discipline in a satisfactory way, starting from Game Rises and Descends, where it is the main focus of the work. In order to reach this proposal, a written evaluation was carried out with the group of 6 th B of 2017, with mathematical contents involving the four fundamental operations of mathematics, where it was found a great difficulty in solving the questions. He then listens to the group's accompaniment with workshops using the mathematical game "Sobe descends", seeking to work the fundamental operations, and the material for the elaboration of the game was of the own locality (bucha do miriti) involving the culture of these students. At the end of the workshops, a written evaluation was carried out, working with the same questions as the first evaluation, in order to evaluate their development in the four operations. Thus, the purpose of the work is to help the student with the contents that are emphasized in calculations with the fundamental mathematical operations, through workshops given, so that the latter can assimilate and put into practice when necessary such contents, thereby losing the fear of discipline mainly at the beginning of elementary school major, 6th grade.